Principles of measurement and transduction of biomedical variables - Button, Vera Lucia da Silveira Nantes (Academic Press, an imprint of Elsevier, 2015)
Principles of Measurement and Transduction of Biomedical Variables is a comprehensive text on biomedical transducers covering the principles of functioning, application examples and new technology solutions. It presents technical and theoretical principles to measure biomedical variables, such as arterial blood pressure, blood flow, temperature and CO2 concentration in exhaled air and their transduction to an electrical variable, such as voltage, so they can be more easily quantified, processed and visualized as numerical values and graphics. The book includes the functioning principle, block diagram, modelling equations and basic application of different transducers, and is an ideal resource for teaching measurement and transduction of biomedical variables in undergraduate and postgraduate biomedical engineering programs. Will help you to understand the design and functioning of biomedical transducers through practical examples and applied information Covers MEMS and laser sensors Reviews the range of devices and techniques available plus the advantages and shortcomings for each transducer type.